Sickle cell vaso-occlusive crisis: it's a gut feeling. Issue 1 (December 2016) - Lim, Seah; Fast, Loren; Morris, Alison
Abstract Insights in the pathogenesis of vaso-occlusive crisis in patients with sickle cell disease have changed significantly in the last decade. Various laboratory and clinical evidence have provided support to the pivotal role of activated neutrophils in this process. A recent study in murine sickle cell disease indicated that the intestinal microbiota is responsible for regulating the number of aged neutrophils, a subset of neutrophils that are overly activated. Reduction of these neutrophils in vivo protected the mice from fatal TNFα-induced vaso-occlusive crisis. In this paper, we discuss the reasons why patients with sickle cell disease may have an abnormal intestinal microbiota and how this could contribute to the development of vaso-occlusive crisis. We also highlight the recent interest in studying the intestinal microbiota of patients with sickle cell disease and suggest that the next therapeutic approach for these patients may well be in the manipulation of the intestinal microbiota to restore the individual's microbial landscape.